Rapid spatially-resolved post-synthetic patterning of metal–organic framework films. Issue 38 (13th April 2021) - Al-Ghazzawi, Fatimah; Conte, Luke; Wagner, Klaudia K.; Richardson, Christopher; Wagner, Pawel
Abstract : Reactive inkjet printing post-synthetically patterns MOF films rapidly and controllably. Abstract : Reactive inkjet printing was used for fast and facile spatially-controlled post-synthetic patterning of metal–organic framework films. Here, we report use of the reactive inkjet printing technique to rapidly produce patterned electroactive MOF films by covalent attachment of redox-responsive ferrocenyl groups to UiO-66-NH2 on FTO glass. This study paves the way for the wide applicability of reactive printing to MOF film modification.